Belief - Bismark, Joseph; Balagtas, Chandravali dasi; Munian, Muralikrishnan; VStudios ([S.l.] : VStudios, 2007)
Joseph Bismark give talk on the importance of belief in network marketing. Belief take an important roles in motivate and build desire for the people in network marketing
Title from title screen
executive producer, Pathman Senathirajah ; video editor, Bernard Gonzales
DVD format
Keywords: Multilevel marketing; Direct marketing